2007
DOI: 10.1111/j.1365-2222.2007.02703.x
|View full text |Cite
|
Sign up to set email alerts
|

A matrix effect in pectin‐rich fruits hampers digestion of allergen by pepsin in vivo and in vitro

Abstract: The matrix effect in pectin-rich fruits can influence the digestibility of food proteins and thereby the process of allergic sensitization in atopic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 39 publications
2
42
1
Order By: Relevance
“…TLPs were important constituents of the analyzed kiwifruit extracts representing 27 -31% of total proteins. TLPs abundance in the fruits together with the structural features (eight conserved disulphide bridges), and the complex plant-specific tissue matrix [38,39] may contribute to their survival in the gastrointestinal tract and the process of allergic sensitization. This is the first mAb-based sandwich ELISA developed for the quantification of the kiwi TLP allergen.…”
Section: Discussionmentioning
confidence: 99%
“…TLPs were important constituents of the analyzed kiwifruit extracts representing 27 -31% of total proteins. TLPs abundance in the fruits together with the structural features (eight conserved disulphide bridges), and the complex plant-specific tissue matrix [38,39] may contribute to their survival in the gastrointestinal tract and the process of allergic sensitization. This is the first mAb-based sandwich ELISA developed for the quantification of the kiwi TLP allergen.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the food matrix may contain substances able to hamper enzymatic digestion by making physical obstacles to enzyme action. Those described so far are lipids, e.g., phosphatidylcholine [8,24] secreted in the stomach and also abundant in milk, as well as polysaccharides, e.g., pectin in fruit matrices [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…When the digestibility of kiwi, banana, apple, and sour cherry TLPs were compared in vitro, kiwi TLP was the only gastric labile protein, being readily digested by pepsin within several minutes [28].…”
Section: Introductionmentioning
confidence: 99%
“…The immunoreactivity of hydrolysis products in dialysates was considerably reduced by polysaccharides. Polovic et al (Polovic et al, 2007) demonstrated that addition of apple fruit pectin (1.5% and 3%) to the purified kiwi allergen Act c 2 was able to protect it from pepsin digestion in vitro. In vivo experiments on healthy non-atopic volunteers have shown that 1 h after ingestion of kiwi fruit in gastric content intact Act c 2 was still present.…”
Section: Noncovalent Modificationsmentioning
confidence: 99%